Malaysian researchers turn pineapple waste into drones, liquid cleansers and more - Sheela, Chandran (Star Media Group Berhad, 2022)
Malaysia is one of the world’s largest producers of pineapple; the industry brings in over RM600mil to the country’s economy, according to the Malaysian Pineapple Industry Board (MPIB).